SUPPLY CHAIN SELF-RELIANCE AND PRICE STABILITY IN CULINARY MICROENTERPRISES: A STRUCTURAL RESPONSE - Dewi Permata Sari; Waluyo Waluyo; Mahmudulhassan Mahmudulhassan (Universitas KH. Abdul Chalim Mojokerto, 2026)
Market distortions and volatility in food raw material prices place culinary microenterprises in a vulnerable position due to their limited control over cost structures. This study aims to explain how upstream supply chain self-reliance is developed as a structural response to market distortions in culinary microenterprises. Employing a qualitative approach with a case study design, this research examines Warung Mie Ayam Bakso Putra Kelana in Krui, Lampung. Data were collected through in-depth interviews with the business owner and supporting informants and were analyzed using thematic analysis based on a conceptual framework. The findings reveal that upstream sector integration through self-managed cattle farming, feed management and slaughtering processes in accordance with halal standards, as well as the development of a chili cultivation plot, functions as an internal buffering mechanism against price volatility. Such supply chain self-reliance limits the transmission of market price fluctuations to the internal cost structure, enabling the enterprise to maintain price stability and operational sustainability amid volatile input prices. This study contributes a case-based conceptual insight into the role of upstream supply chain self-reliance as an internal stabilization mechanism for culinary microenterprises operating within distorted food markets.